How meteorological factors impacting on scrub typhus incidences in the main epidemic areas of 10 provinces, China, 2006–2018 - Luo, Yizhe; Zhang, Longyao; Lv, Heng; Zhu, Changqiang; Ai, Lele; Qi, Yong; Yue, Na; Zhang, Lingling; Wu, Jiahong; Tan, Weilong (Frontiers in Public Health, 2022)
Scrub typhus, caused by Orientia tsutsugamushi, is a serious public health problem in Asia-Pacific region, threatening the health of more than one billion people worldwide. China is one of the countries with the most serious disease burden of scrub typhus. Previous epidemiological evidence indicated that meteorological factors may affected the incidence of scrub typhus, but with limited evidence of correlation between local natural environment factors dominated by meteorological factors and scrub typhus. This study aimed to evaluate the correlation between monthly scrub typhus incidence and meteorological factors in areas with high Scrub typhus prevalence using a distributed lag nonlinear model (DLNM). The monthly data on scrub typhus cases in ten provinces from 2006 to 2018 and meteorological parameters were obtained from the Public Health Science Data Center and the National Meteorological Data Sharing Center. The results of the single-variable and multiple-variable models showed a nonlinear relationship between incidences and meteorological factors of mean temperature (Tmean), rainfall (RF), sunshine hours (SH), and relative humidity (RH). Taking the median of meteorological factors as the reference value, the relative risks (RR) of monthly Tmean at 0 ℃, 46% RH, and 800 mm RF were most significant and RR were 2.28 (95% CI: 0.95-5.43), 1.71 (95% CI: 1.39-2.09), and 3.33 (95% CI: 1.89-5.86). In conclusion, relatively high temperature, high relative humidity, and favorable rainfall were associated with an increased risk of scrub typhus.